GAMBARAN FAKTOR PENYEBAB ASFIKSIA NEONATORUM PADA BAYI BARU LAHIR DI RSUD dr. R. GOETENG TAROENADIBRATA PURBALINGGA TAHUN 2014 - Fajar Setiawati; Rosi Kurnia Sugiharti (Viva Medika, 2015)
Background: In Indonesia in 2007, the infant mortality 34 / 1,000 births. One ofthe causes of respiratory disorders (asphyxia neonatorum) 37%. Data in dr. RGoeteng Taroenadibrata Year 2010 - 2011 out of 2427 deliveries, a total of 119cases of asphyxia neonatorum (4.90%) cases. Objective: To determine factors that cause asphyxia Neonatorum picture of thenewborn in dr. R. Goeteng Taroenadibrata Purbalingga Year 2010-2014Methods: Retrospective descriptive quantitative approach. Purposive samplingtechnique samples, types of data collection instruments Secondary master datatables, univariate analysis. Results: The incidence of asphyxia neonatorum in the newborn in dr. R GoetengTaroenadirata Purbalingga years 2010 - 2011 was 102 cases, 17 cases meetingcriteria for exclusion, died 18 (0.74%) cases from 2427 deliveries. Based largelydue to maternal factors Membranes Premature Rupture of 27 cases (26.5%).Based largely due to factors Placenta Placental abruption 3 cases (2.9%). Basedon Fetus factors caused coil cord 7 cases (6.9%). Based Neonatal factors largelydue to premature babies 12 cases (11.8%). Conclusions: Factors that cause asphyxia Neonatorum largely due to prematurerupture of membranes, placenta abruption, nuchal cord, Premature Babies.Keywords: Causes of asphyxia neonatorum, Newborn